1992
DOI: 10.1042/bj2830591
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the NADPH-dependent H2O2-generating system in pig thyroid particulate fraction by limited proteolysis and Zn2+ treatment

Abstract: The NADPH-dependent H2O2-generating system in a pig thyroid particulate fraction requires micromolar concentrations of Ca2+ for activity. The H2O2 generator could be Ca(2+)-desensitized (i.e. made fully active in the absence of Ca2+) by limited proteolysis with alpha-chymotrypsin or by treatment with ZnCl2. The Zn2+ effect was temperature- and dose-dependent with an apparent half-maximum concentration of 0.15 mM at 40 degrees C. Ca2+ desensitization was not reversed by adding the Zn2+ chelators, 1,10-phenanthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
4
11
0
1
Order By: Relevance
“…This might reflect the importance of the Duox C terminus as control mechanism for Ca 2ϩ binding or for termination of the electron flow. Limited proteolysis of thyroid NADPH oxidase by ␣-chymotrypsin results in irreversible, calcium-independent H 2 O 2 production (40). These data together with our observation support the idea that Duox activity might be regulated via the displacement or conformational change of an inhibitory domain.…”
Section: Discussionsupporting
confidence: 78%
“…This might reflect the importance of the Duox C terminus as control mechanism for Ca 2ϩ binding or for termination of the electron flow. Limited proteolysis of thyroid NADPH oxidase by ␣-chymotrypsin results in irreversible, calcium-independent H 2 O 2 production (40). These data together with our observation support the idea that Duox activity might be regulated via the displacement or conformational change of an inhibitory domain.…”
Section: Discussionsupporting
confidence: 78%
“…We previously reported that Ca2+ controls NADPH oxidase activity by acting directly on an autoinhibitory domain, or inhibitory protein component [27]. This study shows that the enzymatic activity remains Ca'+ dependent, despite treatment with detergent and 2 M KC1.…”
Section: Discussionmentioning
confidence: 68%
“…Regulation of Duox by Ca 2+ probably occurs via its paired EF‐hand motif. It has been reported that limited proteolysis with α‐chymotrypsin renders thyroid NADPH oxidase fully and irreversibly active independently of Ca 2+ [65]. This implies that the Ca 2+ ‐binding EF‐hands of Duox serve as an autoinhibitory domain, whereas those of Nox5 function as an activation domain [66].…”
Section: Regulation Of Nox‐family Enzymes By Ca2+mentioning
confidence: 99%